Exploring children’s stigmatisation of AIDS-affected children in Zimbabwe through drawings and stories - Campbell, Catherine (Pergamon, 2010)
AIDS-related stigma is a major contributor to the health and psychosocial well-being of children affected by AIDS. Whilst it is often suggested that AIDS-affected children may be stigmatised by other children, to date no research focuses specifically on child-on-child stigma. Using social representations theory, we explore how Zimbabwean children represent AIDS-affected peers, examining (i) whether or not they stigmatise, (ii) the forms stigma takes, and (iii) the existence of non-stigmatising representations that might serve as resources for stigma-reduction interventions. Our interest in identifying both stigmatising and non-stigmatising representations is informed by a theory of change which accords a central role to community-level debate and dialogue in challenging and reframing stigmatising representations. In late 2008, 50 children (aged 10–12) were asked to “draw a picture of a child whose family has been affected by AIDS in any way”, and to write short stories about their drawings. Thematic analysis of stories and drawings revealed frequent references to stigmatisation of AIDS-affected children – with other children refusing to play with them, generally keeping their distance and bullying them. However children also frequently showed a degree of empathy and respect for AIDS-affected children’s caring roles and for their love and concern for their AIDS-infected parents. We argue that a key strategy for stigma-reduction interventions is to open up social spaces in which group members (in this case children) can identify the diverse and contradictory ways they view a stigmatised out-group, providing opportunities for them to exercise agency in collectively challenging and renegotiating negative representations. Contrary to the common view that drawings enable children to achieve greater emotional expression than written stories, our children’s drawings tended to be comparatively stereotypical and normative. It was in written stories that children most eloquently expressed meanings and emotions, and an awareness of the complexity of the scenarios they portrayed.